Beyond the “Yellowstone Model:” The Origins of National Parks in Brazil and Argentina - Kaltmeier, Olaf; Freitas, Frederico (Historia Ambiental Latinoamericana y Caribeña (HALAC) revista de la Solcha, 2021)
Book ReviewKaltmeier, Olaf. National Parks from North to South: An Entangled History of Conservation and Colonization in Argentina. Inter-American Studies 34. Trier; New Orleans: WVT Wissenschaftlicher Verlag Trier; University of New Orleans Press, 2021.Freitas, Frederico. Nationalizing Nature: Iguazu Falls and National Parks at the Brazil-Argentina Border. Latin American Studies 122. Cambridge; New York: Cambridge University Press, 2021.